Komposisi Spesies, Kepadatan, dan Ukuran Bintang Laut di Perairan Pantai Leato Selatan, Gorontalo - Merike Modek; Ni Wayan Damayani; Asni Asni; Nur Wiranti; La Nane; Sitti Nursinar (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2022)
This research was conducted in April–May 2021 at three. The purpose of this study was to determine the species composition, density, and size of starfish in South Leato Coastal Waters, Gorontalo. The method used is a random sampling method using a quadratic transect measuring 5 × 5 m, which is placed on coral reefs and Sargassum three times. The results showed that there were three types of starfish in the South Leato Coast, namely Linckia laevigata, Protoreaster nodosus and Culcita novaeguineae. Consecutively higher densities of starfish were species (L. laevigata, P. nodosus and C. novaeguineae). The higher body height of the starfish is species (C. novaeguineae, P. nodosus and L. laevigata), while the higher body diameter is species (P. nodosus, L. laevigata, and C. novaeguineae).